2017
DOI: 10.1504/ijea.2017.10013442
|View full text |Cite
|
Sign up to set email alerts
|

US airline stock market performance and change in investor behaviour over the great recession of 2008

Abstract: We study the relationship of West Texas Intermediate (WTI) crude oil returns and the stock market returns with the US airline stocks before, during and after the 2008 financial crisis. We confirm the positive relationship of the airline stock returns with the overall market and the negative relationship with WTI. However, we find that the crisis led to a structural change in this relationship. Our results differ for low-cost airlines which absorb the oil price shock better as compared to legacy airlines. We al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
(40 reference statements)
1
1
0
Order By: Relevance
“…It concluded that the impact of inflation exceeded potential gains from money supply in the long run. Wood & Gokhale (2017) confirmed a positive relationship between general stock market returns and airline stock returns.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…It concluded that the impact of inflation exceeded potential gains from money supply in the long run. Wood & Gokhale (2017) confirmed a positive relationship between general stock market returns and airline stock returns.…”
Section: Discussionsupporting
confidence: 55%
“…Using the Engle-Granger cointegration method, they addressed a longterm relation between oil prices and the share prices of major airlines, highlighting the significant monthly adjustment rates in response to deviations. Wood & Gokhale (2017) investigated the stock performance of U.S. airline companies during the 2008 Great Recession. The study found that airline stocks exhibited similar movements to the overall stock market during this period, indicating a correlation.…”
Section: Literature Reviewmentioning
confidence: 99%